ANTI-INFLAMANTORY EFFECTS OF ETYL ACETATE FRACTION OF ETHANOL EXTRACT 96% ON CABBAGE WHITE (Brassica oleracae L.) ON Rat (RATTUS NORVEGICUS L.) By IN VIVO - Rangki Astiani (Fakultas Farmasi Universitas 17 Agustus 1945 Jakarta, 2024)
Inflammation is a complex biological response of vascular tissue for the presence of danger, such as pathogens, cell damage or irritation. This study aims to determine anti-inflammatory activity of ethyl acetate fraction extract of leaves of white cabbage (Brasiccaoleracea L). This study using white rats Wistar lane and were divided into 5 groups, consisting of a negative control (CMC Na 0,5%), positive control (Diclofenac Sodium 13.5 mg / kg), and dose I, II and III consisting of a suspension of ethyl acetate fraction of white cabbage leaves with a dose of 250 mg / kg, 500mg / kg and 750mg / kg. The results showed fraction of ethyl acetate extract of white cabbage can reduce the volume of edema in the legs of mice induced with karegenan have an effect at a dose of 250mg / kg BW and 500 mg / kg BW.